Nauczyciel jako kluczowy element środowiska edukacyjnego małego dziecka w nauczaniu matematyki - Dobrowolska, Małgorzata (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Mathematics occupies a special position in the contemporary education. As a common language of man and nature, it is a crucial subject for the student’s future career in a world dominated by technology. On the other hand, it plays a social function adequate for its royal title: as befits a true queen, it ennobles or degrades, perpetuates the existing hierarchy or reshuffles it, punishes and rewards, disciplines and liberates. Research shows that a small child is a born mathematician, and a vast majority of kindergarten children show predispositions to learning this subject. Despite this fact, a widely shared belief sees mathematics as a knowledge for the chosen ones, and similar surveys, carried out for older pupils, seem to confirm this notion. In this paper, we propose a way out of this apparent paradox, by re-defining the role of a teacher in the mathematical education of a small child.
Keywords: early school education; mathematics; math for children; math teacher; preschool education teacher; young child